Problematika Guru Dalam Pelaksanaan Kelas Luring Selama Pandemi Covid-19 - Dina Ramba; Eky Setiawan Salo (Jurnal Keguruan dan Ilmu Pendidikan, 2021)
This research in discussing the problems of teachers in the implementation of offline classes during the covid-19 pandemic in the Thematic Learning of Class 1 students at SDN 352 Sasak, Bittuang District, Tana Toraja Regency. This research is a qualitative. Data collection techniques used are observation, interviews and documentation. The results of this study illustrate that the implementation of offline learning has started well because the offline learning process is carried out through three stages, namely the planning, implementation and evaluation stages. at the planning stage the teacher makes RPP at the beginning of each semester, the implementation stage carries out visits/study assistance at students' homes then the evaluation stage is by giving assignments. However, in the offline learning process applied by the teacher, the teacher experienced several problems in the learning process, including the time given to the learning process which made it difficult for the teacher to convey the material as a whole, the application of social distancing for first graders was very difficult to implement and the last access was in the form of vehicles and travel costs. to be used in visiting each group of students.